2019
DOI: 10.6007/ijarbss/v9-i1/5463
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Task-Based Learning: Developing Speaking Skill and Increase Motivation via Instagram

Abstract: The ability to communicate fluently and accurately is becoming one of the most important components of language elements in Malaysia. Some of the factors that cause to the inability to speak eloquently are low self-confidence, inadequate practices and less exposure to the language. Henceforth, this action research aimed to discover the potential use of integrating Instagram features and task-based learning activities to develop speaking skills and identify the level of pupils' motivation. In this study, an obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 8 publications
3
32
0
Order By: Relevance
“…Broadly, many researchers admit that the use of task-based learning has some promising effects such as motivating, stimulating, empowering, and challenging students during the learning process. Beside motivating students, the integration of task-based activities in a language learning has proven in enhancing students' self-confidence to deliver their ideas in reality (Afifah Binti Azlan et al, 2019). These characteristics are needed by students to gain autonomy in language learning.…”
Section: Introductionmentioning
confidence: 99%
“…Broadly, many researchers admit that the use of task-based learning has some promising effects such as motivating, stimulating, empowering, and challenging students during the learning process. Beside motivating students, the integration of task-based activities in a language learning has proven in enhancing students' self-confidence to deliver their ideas in reality (Afifah Binti Azlan et al, 2019). These characteristics are needed by students to gain autonomy in language learning.…”
Section: Introductionmentioning
confidence: 99%
“…The roadmap of language teaching and learning has experienced major changes in the era of deployment of new technologies worldwide (Azlan et al, 2019). Nowadays the 21st century world, mobile technology with the integration of interactive Web 2.0 Internet based-applications better known as online social media is becoming more apparent and vibrant in our lifestyles.…”
Section: Introductionmentioning
confidence: 99%
“…Although English is taught to students since pre-school, the proficiency level especially in the writing skills such as the use and application of correct tenses, writing sentence structure, punctuation, vocabulary usage and other grammar forms among ESL primary pupils in rural areas are still significantly low (Azlan et al, 2019). Thus, to accommodate the weak students in their writing ability, it is necessary for the teachers to acquire the skill of integrating technological platforms such as social media with the writing task to be used both inside and outside classroom learning.…”
Section: Introductionmentioning
confidence: 99%
“…There are few studies conducted in Indonesia and Columbia (Vaca Torres & Gómez Rodríguez, 2017;Riswandi, 2018). Since there were limited past studies conducted in Malaysia which related to the intervention of Gold Standard PBL mentioned in the proposed study, therefore a few past studies in using PBL to improve speaking skill in Malaysia context were taken as example (Azlan, Zakaria, & Yunus, 2019;Baruah, 2012).…”
Section: The Use Of Pbl For Pupils' Speaking Skillmentioning
confidence: 99%
“…PBL has been widely used by educator but the published journal related to Gold Standard PBL Framework by Buck Institute Education (2015) is still quite limited in Malaysia. In this new world of 4 th industrial revolution, the delivery of knowledge or education are depending on the evolving technologies and generating new styles of teaching and different ways of assessment Azlan et al (2019). Therefore, a study by Azlan et al (2019) suggested an integration of Instagram and task-based learning to be a medium for pupils to practice their speaking skill.…”
Section: Related Past Studies On Using Project Based Learning To Enhamentioning
confidence: 99%